Sustainable Management of Guruh Gemurai Waterfall Ecotourism in Kuantan Singingi - Thamrin Thamrin; Ridwan Manda Putra; Nofrizal Nofrizal; Rahman Karnila (Riau University, 2020)
Tourism Location of Guruh Gemurai Waterfall, Kuansing is one of the most beautiful tourist destinations to visit, which is located in Kuasing Regency, Riau. The study is conducted from September to October 2010. To see the sustainability of this tourist area, research was carried out to identify current environmental conditions. Factors for future development and assessing the ecotourism sustainability of Guruh Gemurai Waterfall using a survey. From the research results, it is found that many factors need to be improved by the management, especially those related to the safety of visitors, especially the stairs and handrails at level 4, the facilities besides being equipped with representative trash cans. It is recommended that the seven levels be managed, then all that is available must be developed again, both the damaged ones and the new ones, which must be remade so that it affects labor absorption. From the leveraging factors, there are six: covering the basic water substrate, water conditions, having protected species, local labor absorption, environmental knowledge, and growth in the number of traders. However, from these six leveraging factors, there are only three factors that can be improved, namely local labor absorption, environmental knowledge, and growth in the number of traders.